Low burnout and high engagement levels in athletic trainers: results of a nationwide random sample - Giacobbi, P. R. (Journal of Athletic Training, 2009)
Objective: To assess the prevalence of occupational burnout, engagement, and somatic health complaints and the associations among these constructs experienced by certified athletic trainers (ATs). A secondary objective was to examine differences between men and women, those with more versus less postcertification experience, and ATs who worked in different occupational settings.